Atenção à saúde mental na Estratégia Saúde da Família no Município de Parnamirim/RN: opinião dos profissionais, dos portadores de transtornos mentais e seus acompanhantes - Dutra, Samia Valeria Ozorio (2012)
This study aims to analyze and compare the opinion of professionals, managers and users about the mental health care in the Family Health Strategy (FHS). It is characterized as an Operations Research or Health System Research with a cross-sectional design and a descriptive quantitative nature. The study was developed from the application of the Opinion Measurement Scale allied to techniques of observation and structured interview in the city of Parnamirim / RN. The sample consists of 409 subjects, 209 professionals of the Family Health Strategy, 30 of the Oral Health Strategy, 19 of the Family Health Support Center, 24 directors of Basic Health Units, plus 68 users with mental disorders and 59 caregivers, respecting the ethical parameters of Resolution 196/96 of the National Health Council, trial registration number: CAAE 0003.0.051.000-11. Quantitative data were submitted to the Epi-info 3.5.2 for analysis. The network of mental health in Parnamirim involves the flow between the FHS, Psychosocial Care Centers, clinics and hospitals, having as main barriers the fragility of the referral and counter-referral system, of the municipal health conferences, of the FHS teams by the limitations in material and human resources as well as the population´s lack of acknowledge about the organization of the mental health network, issues that affect the integral attention. Even though the FHS professionals recognize the importance of their actions, they question their role in mental health care, experiencing difficulties in accessing psychiatric services (76.5%). Although most agree that the mentally ill is best treated in the family than in hospital (65.2%), the community health workers were the predominant category in the partial or total disagreement of this statement (40.8%), who is the professional in greater contact with the family. Nevertheless the caregivers miss the support of the FHS as the main focus of attention is on revenue control. The views of professionals, mental patients and caregivers converged in several statements, showing the main weaknesses to be focused by the mental health network of the city, as the perceptions that: (a) physical strength is needed to take care of mental patients for its tendency to aggression, requiring it to stay in the sanatorium for representing danger to society, (b) only a psychiatrist can help the person with emotional problems, (c) the user of alcohol and drugs does not necessarily develop mental illness, (d) the access barriers and doubts about the quality of psychiatric services, (e) caring of a mental health patient does not bring suffering to professionals. Therefore, the commitment to consensus building, monitoring and evaluation of the network are important mechanisms for an effective management system, reflecting in the importance of strengthening the health conferences and approximating different institutions. The results reinforce the importance of strengthening primary care through programs of continuing education focusing on the actions and functions of professionals in accordance with its competences and duties what contribute to the organization and response of mental health care, favoring user´s care and the promotion of family health